AI-assisted language learning in education: ESL perceptions and challenges of ChatGPT - Robert, Jenna Desiree; Joseph, Aries Henry; Apolonius, Lindey Easter (Universiti Teknologi MARA, Kedah, 2025)
Integrating artificial intelligence (AI) into educational settings has generated extensive interest in recent years. ChatGPT, the most recent communication trend in AI, has sparked both interest and criticism in higher education. Numerous studies on the usage of ChatGPT have been undertaken; however, additional study is needed. One area where AI has shown potential is in assisting students with their tasks. Participants in this study were given the opportunity to work with their peers in completing their assignment, in accordance with Vygotsky's notion of social interactions for language development. The goal is to look at how students perceive the use of ChatGPT as a tool for completing assignments during collaborative work. The session’s focus was on assisting the participants on exploring ChatGPT in finding information by the use of questions as prompts. The data for the study was obtained using a convenience sample method. The descriptive analysis of quantitative survey data was performed using the Statistical Package for the Social Sciences (SPSS) software version 25. The students enjoyed the ChatGPT course that was personalized to them. In contrast, the study found that the most important considerations while utilising ChatGPT were providing relevant prompts (questions to assist the search activities) and having a stable internet connection.This study discovered that users may require further training and support to become more comfortable with ChatGPT's features, as well as to improve their ability to search for information by the use of prompts which can expedite their search.